The ASQ certified quality engineer handbook - Laman, Scott A., 1962- (ASQ Excellence, 2022)
"The ASQ Certified Quality Engineer Handbook, Fifth Edition, covers a wide range of topics in the quality engineering field and is organized to align with the 2022 ASQ Certified Quality Engineer (CQE) Body of Knowledge (BoK). This handbook is essential for candidates preparing for the ASQ CQE examination. For working engineers, it is a convenient and thorough guide to the profession. In addition to providing detailed explanations of each section of the 2022 CQE BoK, this current edition includes: 1) new content on cost-benefit analysis, the RACI matrix, assessing risks in auditing, critical to quality characteristics, risk analysis tools, overall equipment effectiveness (OEE), 5 Whys analysis, data automation, and database integration, 2) a new chapter on risk management, 3) appendices and a glossary of terms for reference purposes. Content in this fifth edition has been restructured to provide tools and concepts that match the 2022 CQE BoK, as well as improved textbook and journal article references throughout the entire book. This handbook also provides case studies that give readers a broader context for real-life scenarios and applications."--Back cover.